Composition and Intraspecific Chemical Variability of Leaf Essential Oil of Laggera pterodonta from Côte d'Ivoire. Issue 1 (13th December 2019) - Kambiré, Didjour Albert; Brice Boti, Jean; Yapi, Thierry Acafou; Ouattara, Zana Adama; Paoli, Mathieu; Bighelli, Ange; Tomi, Félix; Casanova, Joseph
Abstract: The chemical composition of 44 leaf oil samples of Laggera pterodonta (DC.) Sch.Bip. ex Oliv. (Asteraceae) from Côte d'Ivoire was investigated, using combination of chromatographic (GC‐FID) and spectroscopic (GC/MS, 13 C‐NMR) techniques. Two oil samples chosen according to their chromatographic profiles were submitted to column chromatography and all fractions of CC were analyzed by GC‐FID, GC/MS and 13 C‐NMR. In total, 83 components accounting for 96.5 to 99.4 % of the whole chemical composition were identified. Significant variations were observed within terpene classes: monoterpene hydrocarbons (0.4–22.7 %), oxygenated monoterpenes (32.9–54.9 %), sesquiterpene hydrocarbons (18.6–38.3 %) and oxygenated sesquiterpenes (3.5–38.4 %). Thus, the 44 compositions were subjected to hierarchical cluster analysis (HCA) and principal component analysis (PCA). Two groups were differentiated according to their composition. All the samples contained 2, 5‐dimethoxy‐ p ‐cymene, α ‐humulene and ( E )‐ β ‐caryophyllene among the main components. Other components were present at appreciable contents and allowed differentiation of two groups: sabinene and germacrene D for Group I; 10‐ epi ‐ γ ‐eudesmol and eudesm‐7(11)‐en‐4 α ‐ol for Group II. All the samples collected in Eastern Côte d'Ivoire constituted Group I, while samples collected in the Central area of the country constituted Group II. Abstract :